Efeitos farmacológicos do óleo essencial da Xylopia laevigata (Mart.) R.E. Fries (Annonaceae) em roedores - Queiroz, João Carlos Carvalho (2014)
The genus Xylopia L., family Annonaceae, is recognized for its medicinal properties, among which antimicrobial and cytotoxic activity, and as an important analgesic. The aim of the study was to investigate the antinociceptive and anti - inflammatory effect of the essential oil of X. laevigata (EOX) in rodents. This study was divided into two chapters: in the first is described prospecting patents and the second the antinociceptive and anti - inflammatory effects of EOX. The prospecting was conducted based on patent applications filed at the European Patent Office (Espacenet), the World Intellectual Property Organization (WIPO) and the database of the National Institute of Industrial Property (INPI) of Brazil. The focus of the research was the use of medicinal plants as a therapeutic approach to pain. The keywords used were: Medicinal Plants, pain, Annonaceae and Xylopia laevigata. Faced with evidence and based on the literature, there is a need to investigate the probable antinociceptive and anti-inflammatory essential oil of X. laevigata. For pharmacological evaluation, male Swiss mice (25-35 g) obtained from the Central Animal Laboratory of the Federal University of Sergipe (UFS) were used .After defining the process for obtaining EOX and preliminary pharmacological tests, set up tests to evaluate the antinociceptive activity EOX: writhing test and the formalin test. To evaluate the anti-inflammatory activity of the test paw edema induced by carrageenan, and the test of carrageenan-induced peritonitis were used .To determine the possible involvement of areas of the Central Nervous System (CNS), the animals were treated and ninety minutes, were anesthetized, perfused, the brains extracted and cut into the cryostat . The brain sections were subjected to immunofluorescence protocol for Fos protein. The motor coordination of the animal was assessed by testing the Rota Rod (7 rpm, 180 s). The experimental protocols were approved by the ethics committee of the UFS (CEPA/UFS: 16/11). Thus, we investigated the antinociceptive and anti-inflammatory effects of X. laevigata leaf essential oil (EOX). The phytochemical analysis of EOX showed the presence of γ-muurolene (19.65%), δ-cadinene (10.18%), α-copaene (7.72%), bicyclogermacrene (6.44%), (E)-caryophyllene (5.88%), γ-cadinene (5.18%) and aromadendrene (5.16%) as the main compounds. In mice, the essential oil significantly produced (p < 0.05 or p < 0.001) an antinociceptive effect by reduction in the early and late phases of paw licking and by a reduced writhing reflex (formalin and writhing tests, respectively). The EOX demonstrate Fos label in the olfactory bulb, piriform cortex and periaqueductal gray. Acute administration of EOX exhibited a significant anti-inflammatory activity in the carrageenan-induced leukocyte migration to the peritoneal cavity (peritonitis). This effect was confirmed by the carrageenan-induced hindpaw edema test. Together, our results provide for first-time evidence to show that X. laevigata leaf essential oil reduces nociception and inflammation at least through an activation of CNS areas, mainly periaqueductal gray, and these results provide evidence for the use of this medicinal plant by traditional medicine practitioners in the management of pain and inflammatory disorders.